2020
DOI: 10.1038/s41598-020-73473-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced asthma-related fibroblast to myofibroblast transition is the result of profibrotic TGF-β/Smad2/3 pathway intensification and antifibrotic TGF-β/Smad1/5/(8)9 pathway impairment

Abstract: Airway remodelling with subepithelial fibrosis, which abolishes the physiological functions of the bronchial wall, is a major issue in bronchial asthma. Human bronchial fibroblasts (HBFs) derived from patients diagnosed with asthma display in vitro predestination towards TGF-β1-induced fibroblast-to-myofibroblast transition (FMT), a key event in subepithelial fibrosis. As commonly used anti-asthmatic drugs do not reverse the structural changes of the airways, and the molecular mechanism of enhanced asthma-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 77 publications
4
47
1
4
Order By: Relevance
“…We also showed, for the first time, a profound difference in α-SMA mRNA expression between TGF-β-treated HBFs from AS and NA group cultured in 3D collagen gel, even though the changes of their morphology in comparison to unstimulated cells were not observed. However, this effect was less pronounced in 3D collagen gel in comparison to our earlier results with the 2D model (Michalik et al, 2009, Paw et al 2017, Wnuk et al, 2020. It was previously demonstrated that the compliance of collagen gels regulated TGF-β-induction of α-SMA expression in human gingival fibroblasts (Arora et al, 1999).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…We also showed, for the first time, a profound difference in α-SMA mRNA expression between TGF-β-treated HBFs from AS and NA group cultured in 3D collagen gel, even though the changes of their morphology in comparison to unstimulated cells were not observed. However, this effect was less pronounced in 3D collagen gel in comparison to our earlier results with the 2D model (Michalik et al, 2009, Paw et al 2017, Wnuk et al, 2020. It was previously demonstrated that the compliance of collagen gels regulated TGF-β-induction of α-SMA expression in human gingival fibroblasts (Arora et al, 1999).…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, fibroblasts from asthmatics, as in the '2D' model, produce more extracellular matrix proteins (COL1, FN1) when compared to their non-asthmatic counterparts. Similarly to the '2D' model (Paw et al, 2017(Paw et al, , 2018Wnuk et al, 2020), this is due to the increased activation of the TGF-β/Smad2/3 pathway, which is a canonical pathway through which FMT induction occurs. All of the processes described above are less pronounced than in the '2D' model, which may be related to the insufficiently rigid substratum, but the differences between cells from asthmatics and non-asthmatics are evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our longitudinal studies clearly show that populations of the HBF from AS and NA cultured in identical conditions in a serum-free medium display different features affecting their sensitivity to the external TGF-β 1 and FMT potential (20,28,30). In standard in vitro cultures the HBFs AS in response to the TGF-β 1 develop the myo broblastic phenotype characterized by a relatively high level of α-SMA incorporated into stress bers more e ciently than the NA counterparts (23)(24)(25)27,28).…”
Section: Resultsmentioning
confidence: 80%
“…Longitudinal studies on the TGF-β 1 -induced FMT potential (a key event in asthmatic subepithelial brosis) revealed a facilitated ability of the asthmatic HBF populations in standard '2D' cultures for phenotypic shifts (23,25,27,28,30,49), that may indicate the involvement of intrinsic properties of these cells in the regulation of FMT. In this study, we also observed the enhanced FMT potential in the TGF-β 1simulated HBF AS populations in contrast to the NA counterparts, when cells were grown in a monoculture as well as in compatible EMTUs.…”
Section: Discussionmentioning
confidence: 99%